Migraine under treatment: findings from the Americas’ Migraine Observatory Study (AMIGOS) - Lisicki, Marco; Muñoz-Cerón, Joe; Sarmento, Elder Machado; Oliveira, Arao; Valença, Marcelo Moraes; Andrade, Juliana Ramos de; Vélez-Jiménez, Karina; Rodriguez-Leyva, Ildefonso; Giacomozzi, Alex Espinoza; Bancalari, Ernesto; chubaroff , Pablo S; Peres, Mario (Headache Medicine, 2024)
Introduction Migraine patients face significant challenges that limit their access to treatment. Epidemiologic studies conducted in individual countries often lack consistent methodologies, hindering broader interpretation. The Americas' Migraine Observatory Study (AMIGOS) is a Pan-American epidemiological study designed to evaluate the burden and treatment of migraine and other headache disorders across the Americas. Here, we present preliminary data on migraine treatment rates. Objectives To describe the percentage of individuals suffering from migraine in the Americas using acute and prophylactic treatment through a unified sampling methodology at a specific time point. Materials and Methods Data were collected online from a sample representative of the demographic and social characteristics of each country, with a confidence level of 98% and a margin of error of 5%. We conducted both qualitative and quantitative research on key aspects of headaches among 17,037 individuals in 20 countries from Canada to Chile. Migraine diagnosis was made based on the ICHD-3 criteria. Results Overall, 73.3% of migraine patients reported using acute medication for their attacks. Higher percentages of acute medication use were observed in Bolivia (88.2%), while lower rates were found in Brazil (59.8%). Current and past use of preventives were reported by 19.5% and 8.1% of migraine patients, respectively. Preventive use was highest in Peru (42.6%) and lowest in Uruguay (7.2%). Among those who were not taking and had not taken prophylactic medications in the past, 54.7% experienced headaches on four or more days per month. This percentage rose above 60% in Venezuela (64.3%), Guatemala (63.9%), Costa Rica (63.3%), Nicaragua (61.7%), and the USA (60.7%), and was lowest in Uruguay (40.5%). Conclusion This is the first comprehensive Pan-American migraine epidemiological study. Results indicate that migraine is largely undertreated in the Americas, with the most alarming figures related to prophylactic treatment. Improving access to headache care in the region is essential.